2008
DOI: 10.1242/jcs.018432
|View full text |Cite
|
Sign up to set email alerts
|

Sorting nexin-1 defines an early phase of Salmonella-containing vacuole-remodeling during Salmonella infection

Abstract: Supplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 48 publications
5
87
1
Order By: Relevance
“…(iii) SopB recruits the GTPase Rab5 to the SCV membrane, that in turn attracts the Rab5-interacting protein Vps34, a PI3K that generates PI3P in the SCV membrane [47]. The accumulation of this phosphoinositide is necessary for the recruitment of the sorting nexins SNX1 and SNX3, which are important regulators of membrane trafficking [48,49]. SNX1 shifts from its endosomal localization to the site of bacterial entry within the first minutes of Salmonella infection.…”
Section: Biogenesis Of the Salmonella-containingmentioning
confidence: 99%
See 1 more Smart Citation
“…(iii) SopB recruits the GTPase Rab5 to the SCV membrane, that in turn attracts the Rab5-interacting protein Vps34, a PI3K that generates PI3P in the SCV membrane [47]. The accumulation of this phosphoinositide is necessary for the recruitment of the sorting nexins SNX1 and SNX3, which are important regulators of membrane trafficking [48,49]. SNX1 shifts from its endosomal localization to the site of bacterial entry within the first minutes of Salmonella infection.…”
Section: Biogenesis Of the Salmonella-containingmentioning
confidence: 99%
“…This receptor is a late endosome marker involved in delivering soluble lysosomal enzymes to lysosomes. Its absence from the SCV was originally seen as an evidence of lack of SCVlysosome fusion [50], but there are reports that support a model in which SCVs can fuse to lysosomes, and then cationindependent mannose-6-phosphate receptor is removed in an SNX1-dependent manner [49,51,52]. SNX3 associates to specific tubular structures (SNX3 tubules) that last from 30 min to 2 h after invasion and contribute to the recruitment of Rab7 and LAMP1 to the SCV and to the movement of the vacuole [48].…”
Section: Biogenesis Of the Salmonella-containingmentioning
confidence: 99%
“…SopB acts by inhibiting the degradation of epidermal growth factor receptor (EGFR) by lysosomes (Dukes et al, 2006). In a recent study, SopB has been attributed to the disappearance of late endosomal markers by recruiting sorting nexin-1 (SNX-1) which is speculated to down-regulate mannose 6-phosphate receptor from maturing SCV (Bujny et al, 2008). Collectively, the current data pins a role for SopB in diverting SCV trafficking from the endosomal maturation pathway.…”
Section: Maturation and Trafficking Of Scvmentioning
confidence: 72%
“…In the context of SNX1, this is manifest in SopB-dependent overrecruitment and tubulation events leading to the accelerated condensation of the organelle and formation of the adherent SCV (See Figure 2). siRNA-mediated suppression of SNX1 is sufficient to inhibit SCV progression into the cell and had a moderate impact upon the intracellular replication of Salmonella (Bujny, Ewels et al, 2008). Similarly, knockdown of SNX3, which constitutes little more than a PX domain and is found on tubular extensions of the SCV distinct from those of SNX1, inhibits SCV maturation and intracellular replication of Salmonella (Braun, Wong et al, 2010).…”
Section: The Sorting Nexins Coordinate Salmonella Pathogenesismentioning
confidence: 96%
“…Bujney et al demonstrated that one consequence of this was the elevated and sustained accumulation of SNX1 to the newly formed SCV. This in turn results in a grossly exaggerated tubulation event that leads to the rapid contraction of the enveloping SCV to form a tightly-wrapped adherent membrane around the bacterium (Bujny, Ewels et al, 2008). Time-lapse videomicroscopy elegantly demonstrates the precision with which the pathogen is able to manipulate its local environment as the tubulation and condensation of the SCV is not observed on the surrounding constitutive macropinosomes (see Figure 2).…”
Section: Phosphoinositides In Salmonella Infectionmentioning
confidence: 99%